Nutrients intake, milk production, and production costs of dairy goats fed with high proportions of cactus cladodes genotypes Opuntia and Nopalea in association with different forage sources - José Geraldo Medeiros da Silva; Lázaro Henrique de Medeiros Santos; Hildelblano Pereira da Silva; Gustavo José Azevedo Medeiros da Silva; Daniel Barros Cardoso; Guilherme Ferreira da Costa Lima; Airon Aparecido Silva de Melo (Acta Scientiarum. Animal Sciences, 2023)
This study aimed to evaluate the nutrient intake, milk production, and production costs of dairy goats fed diets containing the rations with cactus cladodes (Opuntia stricta or Nopalea cochenillifera) associated with silage (Sorghum bicolor) or Tifton hay (Cynodon spp). Twelve pluriparous Saanen and Anglo Nubiana goats (42.25 ± 5.48 kg) at eight weeks of lactation were used. Treatments lasted 60 days, consisting of four periods of 15 days, distributed in three Latin square (4×4) with four diets. The treatments represented by diets with different associated feed: SSOP (Sorghum Silage + Opuntia); THOP (Tifton hay + Opuntia); SSNO (Sorghum Silage + Nopalea); and THNO (Tifton hay + Nopalea), in addition to concentrate in all diets. There were differences (p < 0.05) for the intakes of DM, OM, with higher values observed for goats fed the diets THNO, THOP, and SSNO, and for CP, NDF and ADF were higher for THNO and SSNO diets. Similar behavior occurred for voluntary and total water intake. The milk production and feed efficiency did not differ (p > 0.05). Costs with food, milk revenue, and gross revenue were not influenced by diets (p > 0.05). The Opuntia or Nopalea cactus cladodes genotypes associated with sorghum silage or tifton hay can be used to feed dairy goats in the semiarid region.